A study of functional outcome in unstable intertrochanteric fractures treated by proximal femoral nailing in Bundelkhand region - Pranjal Mishra; Satish Agarwal; Paras Gupta (Asian Journal of Medical Sciences, 2024)
Background: Intertrochanteric fractures are the most frequent fractures of the hip joint. This is attributed to the increase in the elderly population in our country, along with osteoporosis being prevalent in these populations. Aims and Objectives: The aim of the study is to prospectively analyze the functional outcome of unstable intertrochanteric fractures managed with “proximal femoral nail” (PFN). Materials and Methods: The prospective study was conducted on 48 cases of unstable intertrochanteric in Maharani Laxmi Bai Medical College, Jhansi, between June 2022 and December 2023. Results: In our study, the mean age of the patient is 36.16 and the most common age group is 41–60 years, 33.33%, and >60 years, 41.67%. In forty-eight cases, 37 (77.08%) were male patients, and 11 (22.92%) were female patients. The Harris hip score patients follow-up after 3 months 8 (16.67%) patients of excellent outcomes, 18 (37.50%) patients of good outcomes, 12 (25.00%) of fair outcomes, and 10 (20.83%) patients of poor outcomes. The Harris hip score patients follow-up after 6 months 24 (50%) patients of excellent outcomes, 20 (41.67%) patients of good outcomes, 2 (4.17%) of fair outcomes, and 2 (4.17%) patients of poor outcomes. Conclusion: In unstable proximal femur fractures, PFN is a significant advancement in the treatment of unstable trochanteric fractures which has the unique advantages of closed reduction, preservation of fracture hematoma, less tissue damage, early rehabilitation, and early return to work.